1, 3, 5-Triazine and dithienothiophene-based conjugated polymers for highly effective photocatalytic hydrogen evolution. Issue 13 (10th March 2023) - Yang, Jie; Liu, Yahu A.; Zhai, Ming-Ming; Qin, Jun-Jie; Hu, Wei-bo; Yang, Hui; Wen, Ke
Abstract : Two conjugated organic photocatalysts, thiophene-based TzDTT and thiophene 4, 4-dioxide-based TzDTDO, demonstrate remarkably different photocatalytic hydrogen evolution activities in various reaction solution systems. Abstract : Conjugated microporous polymers (CMPs) have emerged as a class of promising catalysts for photocatalytic hydrogen evolution. In this report, we describe the development of two triazine- and dithienothiophene-based CMP photocatalysts, TzDTT and TzDTDO, both of which were fabricated via Suzuki–Miyaura coupling polymerization. It was found that TzDTT possesses stronger electron donor–acceptor (D–A) ability but a lower photocatalytic hydrogen evolution reaction (HER) rate than TzDTDO in some reaction media. The results indicated that the sulfone groups in TzDTDO play a key role in its superior photocatalytic activity. A HER rate of 26.6 mmol g −1 h −1 was achieved for TzDTDO in a MeCN/H2 O/AA solution under AM1.5G simulated solar light and could be increased to 45.1 mmol g −1 h −1 in the presence of a Pt cocatalyst (3 wt%).